(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
China and India have had cultural and economic relations since ancient times. One of the most important trading routes between India and China, the Silk Road also helped spread Buddhism to East Asia. A China-led economic system in Asia would doom India’s economic prospects, even if India realized it a little late. A forceful economic dissociation replaced a passive commercial disengagement from China after Beijing’s Ladakh invasion. China’s logic of strategic autonomy nudges India to search for strong security alliances with the United States, Europe, Japan, and Australia today. India is looking for ways to work together to establish trustworthy global supply chains that aren’t completely reliant on China. Any nation’s policies must be drastically altered if its territorial integrity or economic success is in danger. The present paper aims to understand the background, present, and future assessment of India-China relations in various dimensions. The paper concludes that the bottom line for the Partnership is quite clear; a peaceful border must prevail if progress accomplished over the previous three decades is to be preserved. As a result, it is impossible to distinguish between the boundary and the future of relationships. The Asian century will be decided by India and China’s ability to find a solution to their differences.